Konsep Nusyūz Dalam Al-Qur’an: (Studi Komparasi Tafsir Jami’ Al-Bayan Dan Al-Qur’an Al-Azhim) - Hidayatullah, Baiq Muhaini (STAI Darul Kamal NW Kembang Kerang, 2023)
This research is an attempt to find out how At-Tabari and Ibnu Katsir view nusyūz. Starting from the many circulating understandings about nusyūz which are only shown and questioned only to women (wives). Understanding that tends to be textual in surah An-Nisa verse 34 is often used as an excuse for committing acts of violence against his wife both physically and psychologically. Even though in fact in Surah An-Nisa verse 128 it is proof that husbands can also do nusyūz. and in the settlement between the two, there is still discrimination against women. This type of research is library research, namely research that is based on data processing obtained from written library materials. Using a comparative approach (muqarin), namely comparing the opinions of At-Tabari in the book jami' Al-Bayan and Ibn Kathir in Tafsir Al-Qur'an Al-Azhim. This study uses the theory of gender equality and liberation theology put forward by Ali Engineer. From this research, it shows that At-Tabari and Ibnu Katsir found that nusyūz of a wife or husband is a form of hatred for a partner and leaves obligations that have been set in household life, and in solving the nusyūz of a wife, there are three stages, namely advising, separating and hitting According to the theology, beatings are only permitted when a wife is proven to have committed adultery. Meanwhile, the settlement of the husband's nusyūz is by peace, and from the liberation theology, a wife is free to file for divorce. Then equality in the settlement of nusyūz which is carried out by the wife can also be carried out in the settlement of the husband's nusyūz.